THE CURRENT CAMP OF THE SOVEREIGN REGULATION OF NEW INNOVATIONS IN UKRAINE - Zastrozhnokova, I.; Ulyanchenko , Yu. (Pressing Problems of Public Administration, 2019)
The article investigates the state and aspects of state regulation of strategic education innovations, planned for 2020–2024. The strategic goals of education in Ukraine for the given period are considered and analyzed. Performance criteria and metrics are reviewed for each goal. The strategic goals of reforming all levels of education in Ukraine are considered: preschool, school, vocational and higher. It is noted that the main strategic priority in pre-school education is to ensure that as many children as possible have access to quality early childhood education. The defined strategy for the development of education states that the MES envisages enrollment of 95% of children from 4 to 6 years of pre-school education, which is intended to stimulate the development of a network of pre-school educational institutions, including private ones. The main objective of secondary school education is to ensure a high level of knowledge, self-sufficiency and creativity among graduates. Among the indicators of the effectiveness of a particular strategic goal, the MES points out: Ukraine’s place in the international study of the quality of PISA education, improvement in reading, mathematics, science and literacy, students’ motivation for learning. Concerning vocational education – the prestige of vocational education in Ukraine should be increased and the number of institutions providing it should be increased. Higher education should become better and be responsible for the future employment of graduates. The necessity of further reformation of the educational network in the newly formed united territorial communities is emphasized, an analysis of the reformation of the educational network on the example of the Azov OTG of the Zaporizhzhya region is added, where the decision on the ownership of the Azov settlement council of the support school and the reorganization of small-scale school complexes was supported educational complexes I-III centuries. Schools I degree with transportation of students 5-11 grades to the support school.